Anthropometry and Nutritional Status of Primary School Children in a Sub-urban Region in Tanzania - Arno Teblick; Sofie De Deken; Wies Vanderbruggen; Marie Vermeersch; Sofie Teblick; Maarten Ruymaekers; Jasmine Andries; Robert Colebunders; Bruno P Mmbando (Shiraz University of Medical Sciences, 2017)
Background: Although undernutrition in children is widely recognized as a major health problem in Tanzania, region-specific prevalence data remain scarce. The objective of the present study was to determine the prevalence of stunting and thinness among primary-school-aged children in a village in the Arusha region in Tanzania, with the aim of developing a targeted nutritional support program. Methods: In the present school-based cross-sectional study, anthropometric measurements were obtained for all children (n = 1,379) who attended Baraa primary school in the Baraa village located at the transition between a rural and urban area in the Arusha region. The data were compared with the world health organization (WHO) 2007 growth reference data for individuals between the ages of 5 to 19. Continuous variables were compared using the t-test, while categorical variables were compared using Pearson's chi-square test. Spearman's correlation and χ 2for trend were used to compare the trend of continuous and categorical variables, respectively. Results: Basic anthropometric values of the study participants were significantly lower than those of the reference population. The mean values of z-scores significantly differed from zero. No gender differences in the prevalence of stunting and thinness were found. Three hundred and twenty-six children (23.7%) suffered from at least one form of undernutrition: 225 (16.3%) were stunted while 156 (11.3%) were thin. The prevalence of both stunting and thinness was at its lowest in the youngest children (5 - 9 years) and highest in the oldest children (14 - 19 years). Furthermore, 54 (16.5%) of the undernourished children suffered from multiple forms of undernutrition. Conclusions: Undernutrition remains prevalent among primary-school-aged children in the Arusha region, Tanzania. Moreover, a high proportion of children suffer from a combination of different forms of undernutrition, with an increase in the prevalence of undernutrition with age.